2013
DOI: 10.4162/nrp.2013.7.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium intake in young Korean adults and its relationship with eating frequency and taste preference

Abstract: Dietary sodium intake is considered one of the major causal factors for hypertension. Thus, to control the increase of blood pressure and reduce the risk of hypertension-related clinical complications, a reduction in sodium intake is recommended. The present study aimed at determining the association of dietary sodium intake with meal and snack frequency, snacking time, and taste preference in Korean young adults aged 20-26 years, using a 125-item dish-frequency questionnaire. The mean dietary sodium intakes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…However, there is little evidence about whether salt taste perception is associated with actual salt intake. Moreover, several previous studies have shown controversial results ( 12 , 13 ). Another simple method to measure salt preference is a person's subjective salt-eating habit.…”
Section: Introductionmentioning
confidence: 96%
“…However, there is little evidence about whether salt taste perception is associated with actual salt intake. Moreover, several previous studies have shown controversial results ( 12 , 13 ). Another simple method to measure salt preference is a person's subjective salt-eating habit.…”
Section: Introductionmentioning
confidence: 96%
“…Our result is clinically meaningful to confirm the harmful effects of a high level of dietary sodium intake in children. The average sodium intake of both the suspected NAFLD and healthy control groups was higher than the recommended reference daily intake, which has been widely reported in studies of adult subjects [45,46]. The possible underlying cause is the Korean preference for high sodium food such as soup, ramen, pickled food and kimchi [45,46].…”
Section: Discussionmentioning
confidence: 85%
“…Potential examples which explain the gender difference in sodium intake include findings in males of increased frequency of eating out, larger portion sizes, and higher salty taste preference [49–51]. A primary reason may be the difference in energy intake between males and females.…”
Section: Discussionmentioning
confidence: 99%